The future of the economy east-west perspectives on pathways through disruption - Powers, John; Khanna, Vikram 1956- (Routledge studies in the modern world economy, 2019)
"Taking a multi-dimensional view, this book synthesizes the main issues and dilemmas facing the economy of the future, seeks to frame the trade-offs in policy terms, while also advancing the discussion towards recommendations and solutions. It focuses on the intersection of work, technology, society, infrastructure, and the economic role of government. In this way, the book is centered on some of the most tangible areas of economic structure that re-produce the gains of growth, but also addresses matters related to the distribution effects and measures that can produce more inclusive and productive outcomes, including the fundamental role of policy and regulation"--